# Calculate the derivative of (x^2-5)^4 - (x^2-5)^3

### 2 Answers | Add Yours

We have to find the derivative of: (x^2-5)^4 - (x^2-5)^3

y = (x^2-5)^4 - (x^2-5)^3

use the chain rule to find the derivative

y' = [(x^2-5)^4 - (x^2-5)^3]'

=> [(x^2-5)^4]' - [(x^2-5)^3]'

=> 4(x^2 - 5)^3*2x - 3(x^2 - 5)^2*2x

=> 8x(x^2 - 5)^3 - 6x(x^2 - 5)^2

**The required derivative is: 8x(x^2 - 5)^3 - 6x(x^2 - 5)^2**

y' = [(x^2-5)^4 - (x^2-5)^3]'

=> [(x^2-5)^4]' - [(x^2-5)^3]'

=> 4(x^2 - 5)^3*2x - 3(x^2 - 5)^2*2x

=> 8x(x^2 - 5)^3 - 6x(x^2 - 5)^2

like that